KNOWLEDGE, ATTITUDE, PRACTICE AND PREVALENCE OF SOIL-TRANSMITTED HELMINTH INFECTIONS AMONG ADULTS IN SUBURBAN AREAS OF HANOI IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe knowledge, attitude and practice regarding prevention of soil-transmitted helminth infections and to determine the prevalence of these infections among adults in Yen Bai commune and Tay Dang town, Ba Vi district, Hanoi in 2023.Methods: A cross-sectional study was conducted among 298 adults. Data on knowledge, attitude and practice were collected through face-to-face interviews using a structured questionnaire. Stool samples were examined using the Kato–Katz technique to detect helminth eggs.Results: The proportion of participants with adequate knowledge about soil-transmitted helminth prevention was 31%. Ascaris lumbricoides was the most commonly recognized helminth (46.98%), followed by hookworm (32.21%) and Trichuris trichiura (21.81%). About 69.13% reported eating raw vegetables, 18.12% reported walking barefoot during farming activities, and 33.89% reported periodic deworming. Overall good practice was observed in 87% of participants. The prevalence of soil-transmitted helminth infection was 8.05%, with hookworm infection being the most common (7.05%).Conclusion: Knowledge regarding soil-transmitted helminth infections among adults was limited despite relatively good preventive practices. Health education and regular deworming programs should be strengthened to reduce infection risk in the community
Keywords: soil-transmitted helminths, knowledge attitude practice, parasitic infection.